(untitled) (Revista Brasileira de Filosofia da Religião, 2020)
In the present paper we examine the theological element of the YogasÅ«tra and two of the newest provocative interpretations put forward about this issue. Considering initially a few authors whose works were regarded as authoritative during the XXth century, we analyse their critical opinions on the subject. After discussing the main passages in which the notion of Ä«Å›vara appears in the YogasÅ«tra, we examine two relatively recent readings of the YogasÅ«tra that have a direct bearing on the question of how Patanjali’s introduction of Ä«Å›vara should be understood. We discuss Maas’ possition, who, developing a hypotesis originally introduced by Bronkhorst, suggests that the YogasÅ«tra and Vyãsa’s Yogabhãá¹£ya (together known as the PãtañjalayogaÅ›ãstra) should be taken as constituting a unified whole compiled and composed by a single author, possibly Patañjali. We also take into consideration Bryant’s translation and commentary on the YogasÅ«tra, where he asserts that Patanjali was a devotee of a personal god like Ká¹›á¹£á¹‡a, and that his notion of Ä«Å›vara-praá¹‡idhãna can be understood as “devotion to God”. We briefly discuss, finally, the mutual compatibility of these interpretations.